Characterization of Automotive Paint Clear Coats by Ultraviolet Absorption Microspectrophotometry with Subsequent Chemometric Analysis - Liszewski, E.; Lewis, Simon; Siegel, J.; Goodpaster, J. (The Society for Applied Spectroscopy, 2010)
Clear coats have been a staple in automobile paints for almost thirty years and are of forensic interest when comparing transferred and native paints. However, the ultraviolet (UV) absorbers in these paint layers are not typically characterized using UV microspectrophotometry, nor are the results studied using multivariate statistical methods. In this study, measurements were carried out by UV microspectrophotometry on 71 samples from American and Australian automobiles, with subsequent chemometric analysis of the absorbance spectra. Sample preparation proved to be vital in obtaining accurate absorbance spectra and a method involving peeling the clear coat layer and not using a mounting medium was preferred. Agglomerative hierarchical clustering indicated three main groups of spectra, corresponding to spectra with one, two, and three maxima. Principal components analysis confirmed this clustering and the factor loadings indicated that a substantial proportion of the variance in the data set originated from specific spectral regions (230-265 nm, 275-285 nm, and 300-370 nm). The three classes were well differentiated using discriminant analysis, where the cross-validation accuracy was 91.6% and the external validation accuracy was 81.1%. However, results showed no correlation between the make, model, and year of the automobiles.